PERENCANAAN PEMBELAJARAN: PENGERTIAN, TUJUAN DAN PROSEDUR - Ginting, Rahmadani Fitri; Harahap, Ade Erbayani (Cahaya Ilmu Bangsa Institute, 2024)
This article discusses lesson planning using the Dick and Carey model. The aim is to understand the definition, objectives, and procedures involved in this planning. The type of research employed is a conceptual analysis with a qualitative-descriptive approach. The analysis results show that the procedures for lesson planning in the Dick and Carey model consist of several stages: (1) identifying learning needs and establishing general learning objectives, (2) conducting learning analysis, (3) identifying student behaviors and initial characteristics, (4) formulating specific learning objectives, (5) developing criterion-referenced tests, (6) designing learning strategies, (7) developing instructional materials, and (8) designing and implementing formative and summative evaluations. By following these procedures, it is expected that lesson planning can be more systematic and effective in achieving educational goals. Artikel ini membahas perencanaan pembelajaran menggunakan model Dick dan Carey. Tujuannya adalah untuk memahami pengertian, tujuan, dan prosedur dalam perencanaan tersebut. Jenis penelitian yang digunakan adalah analisis konseptual dengan pendekatan kualitatif-deskriptif. Hasil analisis menunjukkan bahwa prosedur perencanaan pembelajaran dalam model Dick dan Carey terdiri dari beberapa tahapan, yaitu: (1) mengidentifikasi kebutuhan pembelajaran dan menetapkan tujuan pembelajaran umum, (2) melakukan analisis pembelajaran, (3) mengidentifikasi perilaku dan karakteristik awal siswa, (4) menetapkan tujuan pembelajaran khusus, (5) menyusun tes acuan patokan, (6) merancang strategi pembelajaran, (7) mengembangkan bahan ajar, dan (8) mendesain serta melaksanakan evaluasi formatif dan sumatif. Dengan mengikuti prosedur ini, diharapkan perencanaan pembelajaran dapat lebih sistematis dan efektif dalam mencapai tujuan pendidikan.